Knowledge, vagueness and logic - Wybraniec-Skardowska, Urszula (Zielona Góra: Uniwersytet Zielonogórski)
The aim of the paper is to outline an idea of solving the problem of the vagueness of concepts. The starting point is a definition of the concept of vague knowledge. One of the primary goals is a formal justification of the classical viewpoint on the controversy about the truth and object reference of expressions including vague terms. It is proved that grasping the vagueness in the language aspect is possible through the extension of classical logic to the logic of sentences which may contain vague terms.
Keywords: vague knowledge; fuzzy sets; rough sets; vague sets; formal logic